Mapping policy preferences - Ian Budge (Oxford University Press, 2001)
Enriching and empowering its readers, this work gives the most detailed and extensive data available on the policies and preferences of key democratic actors: parties, governments, and electors in twenty-five democracies over the whole post-war period. It provides a helpful CD-ROM, documentation and suggested uses for data, as well as extensive background information. Economists, socialists, and historians will find the book highly useful; political scientists, policy analysts, rational choice theorists, and comparativists will find it a must